UHI based Healthcare Management System through Digital Transformation - Patil, Sumit; Khairnar, Rohit; Rane, Keval; Nimje, Pavan; Zala, Dhruvi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The Unified Health Interface (UHI) represents a pivotal initiative within the Indian healthcare landscape, offering an open and interoperable IT ecosystem tailored for modern and innovative health service delivery. In response to the challenges posed by the COVID-19 pandemic, UHI emerges as a strategic solution aimed at ensuring enhanced accessibility and quality of healthcare services. Through its seamless interface, UHI facilitates various functionalities including online search, lab test bookings, virtual medical consultations via video, voice, or chat, digital transfer of health records, and secure digital payments. This paper explores the transformative potential of UHI in addressing the evolving needs of healthcare delivery in India. By fostering ease of application and improving access to quality healthcare services, UHI stands as a cornerstone in the nation’s healthcare infrastructure. The emergence of enterprise- and national-level healthcare systems underscores the growing demand for comprehensive and cost-effective public healthcare solutions. Leveraging classic telecommunications and internet services such as presence, voice, video, and messaging, along with service composition solutions and enterprise networks, UHI lays the groundwork for unified health applications. This research delves into the implications of UHI in driving healthcare accessibility, affordability, and efficiency, while also examining its role in shaping the future trajectory of healthcare delivery in India. By elucidating the integration of UHI within existing healthcare frameworks, this paper provides valuable insights into the transformative potential of digital technologies in revolutionizing public health services.